Exergoeconomic analysis and optimization of wind power hybrid energy storage system - Caifeng Wen; Yalin Lyu; Qian Du; Boxin Zhang; Xuhui Lian; Qiang Wang; Hongliang Hao (Scientific Reports)
Abstract The hybrid energy storage system of wind power involves the deep coupling of heterogeneous energy such as electricity and heat. Exergy as a dual physical quantity that takes into account both 'quantity' and 'quality, plays an important guiding role in the unification of heterogeneous energy. In this paper, the operation characteristics of the system are related to the energy quality, and the operation strategy of the wind power hybrid energy storage system is proposed based on the exergoeconomics. First, the mathematical model of wind power hybrid energy storage system is established based on exergoeconomics. Then, wind power experiments of three forms of thermal-electric hybrid energy storage are carried out, and RSM is used to analyze the power quality and exergoeconomic characteristics of the system, and the optimal working conditions of the experiment are obtained. Finally, an optimization strategy is proposed by combining experiment and simulation. The system efficiency, unit exergy cost and current harmonic distortion rate are multi-objective optimization functions. The three algorithms evaluate the optimal solution based on standard deviation. The results show that the exergoeconomics can effectively judge the production-storage-use characteristics of the new system of ' wind power + energy storage'. The thermal-electric hybrid energy storage system can absorb the internal exergy loss of the battery, increase the exergy efficiency by 10%, reduce the unit exergy cost by 0.03 yuan/KJ, and reduce the current harmonic distortion rate by 8%. It provides guidance for improving the power quality of wind power system, improving the exergy efficiency of thermal-electric hybrid energy storage wind power system and reducing the unit cost.